Effect of pancreas transplantation on the prevention of nephropathy in alloxan-induced diabetic rats - Spadella, C. T. [UNESP]; Mercadante, M. C.S. [UNESP]; Schellini, S. A. [UNESP]; Machado, J. L.M. [UNESP]; Oliveira, W. K. [UNESP]; Bacchi, C. E. [UNESP] (My University, 1996)
We studied the effects of pancreas transplantation on kidney lesions of rats with alloxan-induced diabetes. Ninety inbred male Lewis rats were randomly assigned to 3 experimental groups: group NC included 30 non-diabetic control rats, group DC included 30 alloxan-induced diabetic control rats, and group PT included 30 alloxan-induced diabetic rats that received pancreas transplants from normal donor Lewis rats. Each group was further divided into 3 subgroups of 10 rats which were sacrificed at 1, 3, and 6 months of follow-up, respectively. Clinical and laboratory parameters during these periods were documented. The kidneys of 5 rats in each subgroup were studied and 50 glomeruli and tubules from each kidney were analyzed by light microscopy by two different investigators in a double-blind study. There was progressive glomerular basement membrane thickening (GBMT), mesangial enlargement (ME), and Bowman's capsule thickening (BCT) in kidneys of rats in the 3 experimental groups during follow-up. These alterations were significantly higher in DC rats (GBMT: 1.99 ± 0.31; ME: 2.00 ± 0.33; BCT: 1.88 ± 0.27) when compared to NC (GBMT: 1.54 ± 0.30; ME: 1.56 ± 0.47; BCT: 1.36 ± 0.35) and PT rats (GBMT: 1.49 ± 0.29; ME: 1.57 ± 0.36; BCT: 1.35 ± 0.28) at 6 months (P < 0.01). The extent of GBMT, ME, and BCT observed in DC rats at 1 and 3 months was not significantly different from NC and PT rats. The amount of kidney lesions in PT rats was similar to that of NC rats and lower than those of DC rats at 6 months (P < 0.01). In addition, Armanni-Ebstein lesions of the tubules (AE) and tubular lumen protein (PRO) observed in DC rats were not present in NC or PT rats. We conclude that pancreas transplantation in alloxan-induced diabetic rats prevents the development of kidney lesions beginning at 6 months after transplantation.
Keywords: alloxan-induced diabetes; diabetic nephropathy; pancreas transplantation